Analisis Perilaku Konsumen Dalam Keputusan Pembelian Item Virtual Pada Game Online Valorant - I Made Chandra Mandira; I Dewa Gede Wahyu Dharma Suputra (Universitas Musamus,Merauke,Papua, 2023)
This study aims to find out and analyze how consumer behavior in purchasing virtual items in the Valorant online game is based on five elements of consumer behavior, namely age, occupation and economic environment, lifestyle, personality, and reference group. This research was conducted in the city of Denpasar using a qualitative descriptive approach with a purposive sampling method in selecting informants. Data collection techniques used in this study were observation, interviews and documentation. The results of the study stated that the five elements of consumer behavior consisting of age, work and economic environment, lifestyle, personality, and reference groups can influence informants in making purchasing decisions.